(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The Juvenile Justice System in India is a complex and evolving system aimed at addressing the needs of children who come into conflict with the law. It is governed by the Juvenile Justice (Care and Protection of Children) Act, 2015, which emphasizes the principles of care, protection, development, and rehabilitation of such children. India’s Juvenile Justice System, while progressive in intent, faces several significant challenges that hinder its effectiveness in rehabilitating young offenders and preventing future crime. These challenges stem from a complex interplay of legal, social, and economic factors. Despite the Juvenile Justice (Care and Protection of Children) Act, 2015, there is significant variation in its implementation across different states. This leads to disparities in the treatment of juvenile offenders and undermines the goal of a uniform justice system. Many juvenile justice boards and observation homes lack adequate resources, trained personnel, and specialized facilities to cater to the diverse needs of young offenders. This compromises the quality of rehabilitation programs and the overall effectiveness of the system. The overburdened judiciary often leads to prolonged legal processes, causing undue stress on young offenders and their families. This delay can also hinder the timely implementation of rehabilitation measures.